How does the Phillips curve slope vary with repricing rates? - Emmanuel de Veirman (European Central Bank (ECB), 2023)
In sticky price models, the slope of the Phillips curve depends positively on the probability of price adjustment. I use a series for the empirical frequency of price adjustment to test this implication. I find some evidence that the Phillips curve slope depends positively on the repricing rate. My results support the implication from New Keynesian theory with Calvo pricing that the Phillips curve slope is a convex function of the frequency of price adjustment. However, at all observed values of the frequency of price adjustment, the empirical Phillips curve relation is much flatter than the New Keynesian Phillips Curve at standard parameter values would imply.
Keywords: C22; E31; 330; Inflation; Phillips curve; price setting